“No more brain than a stone”: Hints of Extempore Performance in Shakespeare’s Plays - Oroszlán, Anikó (FOCUS: Papers in English Literary and Cultural Studies, 2014)
Recently, it has become a critical commonplace that theatre and society as well as cultural processes can be analyzed in terms of each other. Social sciences use the metaphors of theatre and drama to describe spectacular social events such as rituals, festivals or games—see, for instance, the works of Erving Goff mann, Victor Turner, Dwight Conquerwood, and Milton Singer. Human behaviour and habits are also frequently defined as performance; the best-known example is probably Judith Butler’s concept of gender performative.1 Very different, however, is the manner in which these approaches treat the relation between power/rules/hegemony and the freedom of the agent who performs. Nonetheless, it is very characteristic that while certain social theories use the metaphors of theatre and performance, others insist that human acts can better be described as improvisation.